Focused on the Family: Development of a Family-Based Intervention Promoting the Transition to Adult Health Care for Adolescents with Type 1 Diabetes - Jaclyn L. Papadakis; Madeleine C. Suhs; Alexander O'Donnell; Michael A. Harris; Lindsay M. Anderson; Kimberly P. Garza; Lindsey Weil; Jill Weissberg-Benchell (MDPI AG, 2024)
Background/Objectives: There is minimal evidence for current interventions promoting the transition to adult healthcare for youth with type 1 diabetes (T1D). Few interventions exclusively target modifiable individual and family-based factors that contribute to transition readiness. The purpose of this paper is to describe the development of Behavioral Family Systems Therapy for Diabetes Transition (BFST-DT), a virtual family-based transition readiness intervention for adolescents with T1D. Methods: The development of BFST-DT occurred in three phases. In phase 1, focus groups with adolescents and young adults with T1D, their caregivers, and pediatric and adult diabetes providers were conducted to assess perspectives on common family challenges surrounding diabetes management and the transition to adult healthcare. In phase 2, focus group data were used to create video vignettes to be used as part of the intervention. In phase 3, BFST-DT was created through the adaptation of a previous evidence-based family intervention for families of adolescents with T1D. Results: BFST-DT is a virtual, 6-month family-based intervention involving four multi-family group meetings and six individual family meetings. It targets the modifiable and reciprocal interactions among individual and family transition readiness factors. Conclusions: BFST-DT is the first family-focused intervention promoting transition readiness in adolescents with T1D and is currently being tested. Intervention development benefits from prioritization of engagement with patients, caregivers, and providers, as their perspectives are invaluable for creating interventions that are relevant and acceptable to communities.